2021
DOI: 10.3389/fcimb.2021.768450
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi trans-Sialidase as a Potential Vaccine Target Against Chagas Disease

Abstract: Chagas’ disease is caused by the protozoan Trypanosoma cruzi, described in the early 20th century by the Brazilian physician Dr. Carlos Chagas. There was a great amount of research devoted to diagnosis, treatment and prevention of the disease. One of the most important discoveries made since then, impacting the understanding of how the parasite interacts with the host’s immune system, was the description of trans-sialidase. It is an unique enzyme, capable of masking the parasite’s presence from the host, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 114 publications
0
8
0
1
Order By: Relevance
“…Several T. cruzi proteins are able to promote cardiac damage in the absence of live parasites by inducing autoimmunity in animal models (Cunha-Neto et al, 1996;Bonney et al, 2011). Fortunately, a number of other recombinant T. cruzi proteins as well as attenuated T. cruzi parasites are emerging as potentially safe strategies for the development of a CD vaccine (Sańchez-Valdeź et al, 2015;Rios et al, 2019;da Costa et al, 2021;Rodrigues da Cunha et al, 2021). Researchers are also testing mRNA vaccines after their successful use in COVID-19 (Diaz-Hernandez et al, 2022;Maldonado et al, 2022).…”
Section: American Trypanosomiasis: Chagas Diseasementioning
confidence: 99%
“…Several T. cruzi proteins are able to promote cardiac damage in the absence of live parasites by inducing autoimmunity in animal models (Cunha-Neto et al, 1996;Bonney et al, 2011). Fortunately, a number of other recombinant T. cruzi proteins as well as attenuated T. cruzi parasites are emerging as potentially safe strategies for the development of a CD vaccine (Sańchez-Valdeź et al, 2015;Rios et al, 2019;da Costa et al, 2021;Rodrigues da Cunha et al, 2021). Researchers are also testing mRNA vaccines after their successful use in COVID-19 (Diaz-Hernandez et al, 2022;Maldonado et al, 2022).…”
Section: American Trypanosomiasis: Chagas Diseasementioning
confidence: 99%
“…Moreover, studies of TSsf-based vaccines have been performed in other animal models like dogs [50][51][52] or monkeys 53 ; however, although promising, they are not enough to reach conclusive results. Within this family, TS-GI proteins have been signaled highly promising candidates (revised by da Costa et al 12 ). However, unlike studies performed with TS-GII, the variability of these antigens was not previously analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…For the TS-GII, which are also among the most used as vaccine antigens, studies about diversity and its possible influence on vaccine performance have been reported only in two studies. 10,11 The TS-GI proteins have also been widely tested as immunogens for T. cruzi vaccines, and they have been pointed out as very promising candidates, 12 however, their diversity has not been analyzed in the context of vaccine development. Moreover, vaccine antigen epitopes should ideally be recognized by the whole HLA diversity of the human population to be protected.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccines for the prevention and control of T. cruzi infection may also be developed using molecules released in EVs. The proteins of T. cruzi ‐derived EVs have been identified as potential vaccine candidates, including members of the TS family, which are involved in invasion processes [48], and the T. cruzi trypomastigote alanine, valine and serine (TcTASV‐C) protein, which plays a role in immune evasion and host–parasite interactions [49]. While these proteins have not yet shown promise as vaccine candidates, the mucin‐like‐associated surface protein (MASP) family, a virulence factor involved in host‐cell invasion, has shown the ability to induce a humoral and cellular response and reduce parasite load when used in immunisation of mice [50].…”
Section: Can Extracellular Vesicles Aid Vaccine Development?mentioning
confidence: 99%